Coexistence of a novel SV2B-ALK, EML4-ALK double-fusion in a lung poorly differentiated adenocarcinoma patient and response to alectinib: a case report and literature review - Chen, Huang; Zhang, Menglan; Bai, Liyan; Niu, Yun; Wang, Xiaowei; Jiang, Ruiying; Wang, Ye; Feng, Qianqian; Wang, Bei; Dai, Tingli; Yuan, Mingming; Chen, Rongrong; et al. (Frontiers in Oncology, 2024)
BackgroundAnaplastic lymphoma kinase (ALK) rearrangement, the most common oncogenic rearrangement in lung adenocarcinoma, occurs in approximately 5% of non-small cell lung cancer (NSCLC) patients. EML4 gene is the most common partner of ALK rearrangement, and distinct EML4-ALK fusions differ in their responsiveness to ALK tyrosine kinase inhibitors. However, the concurrence of two ALK rearrangements in one patient and whose response to ALK-TKIs have rarely been reported so far.Case presentationA 47-year-old Chinese male was diagnosed with stage IV lung adenocarcinoma with multiple intracranial metastases and adrenal metastasis. After progression of two lines of chemotherapy combined with local radiotherapy regimens, his tumor tissue sample was sent to perform the DNA-based next-generation sequencing of 116 genes. Surprisingly, EML4-ALK (E13:A20) fusion and a novel SV2B-ALK (S6:A20) fusion were concurrently identified, which was confirmed using immunohistochemistry and fluorescence in-situ hybridization. Given the superior efficacy of alectinib, the patient received alectinib in the third-line setting with the progression-free survival over 14 months up to now. Moreover, through comprehensive review of previous literatures, a total of 22 patients with multiple ALK fusions and their response to ALK-TKIs were summarized.ConclusionThis is the first report of a NSCLC patient with a novel SV2B-ALK, EML4-ALK double-fusion benefiting from alectinib. Alectinib may be an effective therapeutic option for both primary and metastatic lesions including brain metastases in the late-line setting in NSCLC patients with double-ALK fusion.